2018
DOI: 10.1139/apnm-2017-0370
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low and moderate doses of caffeine supplementation on upper and lower body maximal voluntary concentric and eccentric muscle force

Abstract: Despite the growing quantity of literature exploring the effect of caffeine on muscular strength, there is a dearth of data that directly explores differences in erogenicity between upper and lower body musculature and the dose-response effect. The present study sought to investigate the effects of low and moderate doses of caffeine on the maximal voluntary strength of the elbow flexors and knee extensors. Ten nonspecifically strength-trained, recreationally active participants (aged 21 ± 0.3 years) completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 44 publications
5
39
1
Order By: Relevance
“…Some studies have reported that caffeine ingestion decreases pain perception but without any significant effects on performance [27,37]. Tallis and Yavuz [41] and Sabblah et al [42] did not observe any significant reductions in pain perception, although caffeine ingestion increased muscular strength, suggesting that factors other than the reduced perception of pain contributed to the ergogenic effect. Although two studies reported that improvements in performance were accompanied by a decrease in pain perception [28,29], there was also a decrease in RPE that made it difficult to determine exactly what contributed to the ergogenic effect.…”
Section: Effects Of Caffeine On Pain Perceptionmentioning
confidence: 94%
See 2 more Smart Citations
“…Some studies have reported that caffeine ingestion decreases pain perception but without any significant effects on performance [27,37]. Tallis and Yavuz [41] and Sabblah et al [42] did not observe any significant reductions in pain perception, although caffeine ingestion increased muscular strength, suggesting that factors other than the reduced perception of pain contributed to the ergogenic effect. Although two studies reported that improvements in performance were accompanied by a decrease in pain perception [28,29], there was also a decrease in RPE that made it difficult to determine exactly what contributed to the ergogenic effect.…”
Section: Effects Of Caffeine On Pain Perceptionmentioning
confidence: 94%
“…Using the same doses, Arazi et al [37] observed that caffeine did not improve leg press strength and muscular endurance at either 2 or 5 mg•kg -1 doses. Tallis and Yavuz [41] observed that both 3 and 6 mg•kg -1 caffeine doses were effective for increasing lower-body strength. Furthermore, as stated earlier when discussing power outcomes (section 5), three studies [68][69][70] have investigated the effects of 3 mg•kg -1 of caffeine on resistance exercise performance and power and suggested that this dose can be ergogenic.…”
Section: Caffeine Dose Timing and Habitual Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Acute CAF intake causes a slightly different response to upper and lower body exercise [10], despite the lack of a mechanisms explaining this phenomenon. A recent meta-analysis about the effects of CAF on muscle strength and power output found that CAF significantly improved upper but not lower body 2 of 13 strength [7].…”
Section: Introductionmentioning
confidence: 92%
“…Current research recommends doses of CAF ranging from 3 to 6 mg/kg body mass to elicit ergogenic benefits, while the time of ingestion (from 30 to 90 min before exercise) and the form of ingestion (pills, liquid, chewing gum) are less significant as CAF is rapidly absorbed after ingestion [6]. However, the optimal protocol of CAF supplementation may differ based on the type and duration of exercise, previous habituation to CAF and the type of muscle contraction [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%